Implementasi Teorema Bayes Diagnosa Penyakit Ikan Lele Di Dinas Ketahananpangan Perikanan Rohul - Hendri Maradona; Mi’rajul Rifqi; D Dona; Darmanta Sukrianto; Kiki Yasdomi; Khairul Sabri; Urfi Utami; Muhammad Romi Nst; M Muhammadyodi (Kesatria : Jurnal Penerapan Sistem Informasi (Komputer dan Manajemen), 2024)
Catfish is a freshwater fish that is widely cultivated in almost all parts of Indonesia. This is because catfish is one of the leading commodities, and has good market prospects. In aquaculture, disease attacks can be a threat that causes economic losses, and can even experience large losses in terms of crop yields. Advances in expert systems can overcome the problem by designing a web-based computer system that uses databases and programming languages such as PHP-MySQL so that it can help catfish cultivators to diagnose fish diseases. This study aims to detect disease in catfish using the Bayes theorem method. In this study, there were 13 types of diseases, namely Cotton Wall Disease, White Spots, Yellow Catfish Disease (Jaundice), Itchy Catfish Disease (Trichodiniasis), Rupture of Intestines/RIS (Reptures Intestine Syndrome), Smallpox Disease, Ragged Catfish Disease tail fin, fungal attack, brown blood disease, Enteric septicemia of catfish, columnar disease, proliferative gill disease, channel catfish virus disease. The result of this research is the construction of an expert system that can be used as an early diagnosis of disease in catfish. This system is expected to be developed for diagnosis in other fish, in order to provide greater benefits for its users.